1999
DOI: 10.1177/152660289900600106
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transluminal Angioplasty of the Subclavian Arteries

Abstract: Purpose: To review the feasibility, risks, and long-term results of subclavian artery angioplasty with and without Palmaz stent placement. Methods: Over a 9-year period, 113 patients (67 males; mean age 63 ± 13 years) underwent percutaneous balloon angioplasty of subclavian occlusive lesions for a variety of indications: vertebrobasilar insufficiency (n = 70), upper limb ischemia (n = 50), coronary steal syndrome (n = 6), or anticipated coronary artery bypass grafting using the internal mammary artery in 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 19 publications
4
63
1
Order By: Relevance
“…Although the initial success rate of PTA is high, the long-term angiographic patency is unclear and not ac- ceptable in many reports [26,41]. The use of stents appears to improve both acute and long-term results [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the initial success rate of PTA is high, the long-term angiographic patency is unclear and not ac- ceptable in many reports [26,41]. The use of stents appears to improve both acute and long-term results [42].…”
Section: Discussionmentioning
confidence: 99%
“…For either surgical or endovascular treatment, the indications are as follows: vertebrobasilar ischemia [22][23][24][25], upper limb ischemia, hand "claudication" and digital embolization [12,26,27], both of the preceding [24], angina in patients with a LIMA graft [28,29] and leg claudication in patients with axillo-femoral grafts [29]. Additional indications include increased flow for schedule operative procedure (i.e., LIMA graft, axillofemoral graft, dialysis graft) [30].…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was performed with the brachial artery approach alone in one case due to severe aortic tortuosity and bending. In the femoral artery approach, a pull-through technique 3 was used in two cases. In the femoral artery approach, a standard 9-Fr guiding catheter was used, and in the brachial artery approach, a 6-Fr guiding sheath was used.…”
Section: Methodsmentioning
confidence: 99%
“…A further evolution in the treatment of atherosclerotic lesions of the SATs occurred in the 1980s as percutaneous transluminal angioplasty (PTA) techniques were applied to these lesions. Initially these lesions were treated with PTA alone [6][7][8][9][10][11][12][13], but subsequent studies have reported an improvement in these initial results when stenting implantation was associated to balloon angioplasty [11,[14][15][16][17]. Recent reports, with short and midterm results, suggest that percutaneous treatment of the innominate arteries can be performed with relatively safety and expectations of satisfactory mid-term success [6,[9][10][11][12]18,19].…”
Section: Introductionmentioning
confidence: 99%